Innovative chance discovery for finding innovative useful idea in travelling. (2016) - Lin, Mu-Hua; Hong, Chao-Fu; Lin, Woo-Tsong
If the following enterprises want to enter the blue ocean strategy market with high profits, they need to find the value for new products earlier and take up a position in the new markets. In order to survive for a longer time, enterprises have to find the rare and valuable information at the early stage. To achieve this purpose, the researchers proposed a BCG-based novel innovation classification model. We use KeyGraph algorithms to find the rare keyvalue and the inverse cluster frequency algorithm proposed by this study to conduct two-objective decision analysis. Then, we use the Boston consulting group model to classify keyvalue and inverse cluster frequency's value in which we get the early innovative value. Finally, we used the innovative value to test college freshmen to see the difference between before and after the college freshmen accepted the innovative value. The results show that 59% of the college freshmen perceive the usefulness of the new product, which demonstrates a significant progress. This is to justify that the model proposed by this study can be of help to mine the rare and valuable information early and effectively.